Art 2001 The Problematics Of Apostasy Behavior Post Marriage From The Perspective Of Islamic Law: Islamic Family Law - besse tenri; Nasaruddin; Gasim Yamani (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
Marriage in Islam requires that both spouses share the same religion, namely Islam. In maqasid sharia, it is explained that preserving lineage (hifz al-nasl) must be maintained through lawful marriage and by avoiding adultery. An invalid marriage according to Islamic law may affect the legal status of children born from the marriage, particularly in terms of lineage (nasab), which may be disconnected from the father. Apostasy (riddah) often occurs in individuals who intend to marry someone of a different religion. Due to religious differences, one party may choose to convert to Islam or leave Islam in order to facilitate marriage. Over time, after a long period, a desire may arise to return to the previous religion, resulting in apostasy (riddah). This study aims to identify the factors influencing apostasy and the legal implications of apostasy behavior after marriage from the perspective of Islamic law. The method used is qualitative with a library research approach. Apostasy in marriage can be caused by internal factors such as weak understanding of faith and external factors such as family and environmental influence. Divorce claims may be granted if apostasy leads to disharmony in the household based on the Compilation of Islamic Law (Kompilasi Hukum Islam). In fiqh, apostasy in marriage before consummation (jima’) results in immediate dissolution of the marriage. However, if consummation has occurred, the marriage may be suspended until the end of the iddah period; if the apostate returns to Islam within the iddah period, the marriage remains valid. If not, the marriage is considered dissolved.